Troglitazone metabolism and transporter effects in chimeric mice: a comparison between chimeric humanized and chimeric murinized FRG mice. (13th January 2014) - Samuelsson, Kristin; Pickup, Kathryn; Sarda, Sunil; Foster, John R.; Randall, Kevin; Abrahamsson, Anna; Jacobsen, Matt; Weidolf, Lars; Wilson, Ian
Abstract: 1. The biotransformation, hepatic transporter and blood chemistry effects of troglitazone were investigated following 7 days of dosing at 600 mg/kg/day to chimeric murinized or humanized FRG mice, Mo-FRG and Hu-FRG mice, respectively. 2. Clinical chemistry and histopathology analysis revealed a significant drop in humanization over the time course of the study for the Hu-FRG mice but no significant changes associated with troglitazone treatment in either the Mo-FRG or the Hu-FRG models. No changes in transporter expression in livers of these mice were observed. Oxidative and conjugative metabolic pathways were identified with a 15- to 18-fold increase in formation of troglitazone sulfate in the Hu-FRG mice compared with the Mo-FRG mice in blood and bile, respectively. This resembles the troglitazone metabolism in human and these data are comparable with the formation of this metabolite in the chimeric uPA +/+ /SCID mice. 3. However, larger amounts of troglitazone glucuronide were also observed in the Hu-FRG mouse compared with the Mo-FRG mouse which may be an effect of the drop in humanization of the Hu-FRG mouse during the study. 4. Highly humanized mice have a considerable potential in providing a useful first insight into circulating human metabolites of candidate drugs metabolized in the liver.